REVIEW OF IMPLEMENTATION OF IMMIGRATION INVESTIGATION AND ACTION APPLICATIONS (NYIDAKIM) IN THE CLASS I IMMIGRATION OFFICE OF TPI YOGYAKARTA - Igo Gita Prakasa (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Technology and information systems have played a very important role in people's lives in this era of industrial revolution 4.0. It is undeniable that technology and information systems. Investgation and prosection (Nyidakim) is an application that is used to assist processes in the field of intelligence and immigration enforcement in the form of making examination reports, incident reports, and others. In this case the author focuses on discussing the implementation of the Immigration Investigation and Enforcement application at the TPI Yogyakarta Class I Immigration Office. The implementation of the Application for Immigration Investigation and Enforcement (Nyidakim) at the TPI Yogyakarta Class I Immigration Office is one of the supports in making incident reports, examination minutes, opinion reports, and case decisions. The Immigration Investigation and Enforcement Application can also be accessed by staff to the head of the office at the TPI Yogyakarta Class I Immigration Office, so that each user is granted access rights from the Immigration Investigation and Enforcement Application.